Reviews. Issue 1 (1st December 2015) - Birchall, Michael; Mancke, Carol; Duncan, Adrian
Exhibition as Social Intervention: 'Culture in Action' 1993 (Afterall Exhibition Histories), Joshua Decter and H. Draxler (2013) Köln: Verlag der Buchhandlung Walther Koenig, 192 pp., ISBN: 978-3-86335-448-0, p/bk, €16.80Interactive Contemporary Art Participation in Practice, Kathryn Brown (ed.) (2014) New York: I B Tauris, 297 pp., ISBN: 9781780765518, h/bk, £60.96Dehydrated Landscape of a CONDITION, Reto Pulfer, The Technosphere SEMINARS and Cell texts: Books Written in Prison, Ines and Eyal Weizman, Haus der Kulturen der Welt (the House of World Cultures), Berlin (as part of '100 YEARS OF NOW'), 30 September–4 October 2015